Climate Change and Mitigation Strategies - Sanjay Lote; Vittal Chikalaki; Gayatri Jadhav; Susmita Muttinakantimath; Rakshita Kagawad; Bhavani Yankachi; Bimavva Gadivadar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Climate change presents an unprecedented challenge to humanity, with far-reaching environmental, social, and economic consequences. This paper offers a thorough examination of the phenomenon, exploring its causes, impacts, and mitigation strategies. Beginning with an analysis of the scientific consensus surrounding climate change, including the role of greenhouse gas emissions and their anthropogenic origins, the paper delves into the various manifestations of climate change, from rising global temperatures to extreme weather events.